1994
DOI: 10.1097/00007632-199410150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Injuries in Patients 65 and Older

Abstract: Cervical spine injury commonly occurs with relatively minor trauma in patients > or = 65, with a mortality rate of approximately 26% with associated SCI. Return of functional motor recovery is delayed in older patients with incomplete deficits, but can be expected. C2 injuries, especially odontoid fractures, must be ruled out in older patients with neck pain after even a minor injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
3
12

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 0 publications
6
61
3
12
Order By: Relevance
“…Forty-eight per cent sustained lower cervical spine injuries and 41% injured upper cervical spine (Table 2). Thus our review demonstrated a higher proportion of lower cervical spine injuries than upper cervical spine injuries in the elderly population, which is inconsistent with many other series reporting upper cervical injuries in majority of patients [7,13,18] Neurological injury associated with cervical trauma is less common in elderly patients, due to the higher incidence of odontoid injuries and the more minor nature of the trauma [16]. When a neurological injury does occur in the elderly, it is more commonly incomplete.…”
Section: Discussioncontrasting
confidence: 87%
“…Forty-eight per cent sustained lower cervical spine injuries and 41% injured upper cervical spine (Table 2). Thus our review demonstrated a higher proportion of lower cervical spine injuries than upper cervical spine injuries in the elderly population, which is inconsistent with many other series reporting upper cervical injuries in majority of patients [7,13,18] Neurological injury associated with cervical trauma is less common in elderly patients, due to the higher incidence of odontoid injuries and the more minor nature of the trauma [16]. When a neurological injury does occur in the elderly, it is more commonly incomplete.…”
Section: Discussioncontrasting
confidence: 87%
“…In the sampled population, the clinical pictures were not quite the same as previous reports. 4,8,10 First, the ratio of male patients was similar in both younger and older groups (87% vs 85%). In contrast, most other researchers reported a predominance of females in the elderly.…”
Section: Discussionmentioning
confidence: 87%
“…7,8 Other researchers reported a high proportion of odontoid fracture in the elderly with cervical injuries. 10,12 The strategy for prevention and care for the growing number of elderly people with SCI is thus becoming more important.…”
Section: Introductionmentioning
confidence: 99%
“…Type II odontoid fractures are the most common fractures of the cervical spine in the elderly [11,29,32,44]. Published literature on the radiological outcome in geriatric patients with type II odontoid fractures is scarce.…”
Section: Discussionmentioning
confidence: 99%